Thickness Dependence of Thermoelectric Properties and Maximum Output Power of Single Planar Sb2Te3 Films - Junlabhut, Prasopporn; Nuthongkum, Pilaipon; Harnwunggmoung, Adul; Limsuwan, Pichet; Hatayothai, Chanon; Sakdanuphab, Rachsak; Sakulkalavek, Aparporn (My University, 2022)
P-type Sb2Te3 films with different thicknesses were deposited on polyimide substrates via heat treatment-assisted DC magnetron sputtering. The correlations between the thickness variance and the structure, dislocation density, surface morphology, thermoelectric properties and output power are investigated. As a result, it is clear that the film thickness and the heat treatment process during growth are related to the diffusion of deposited atoms on the substrate surface, leading to imperfection defects inside the films. The imperfections inside the films are affected by their properties. This work also presents the thermoelectric efficiency of a planar single leg of the deposited films with various thicknesses. The maximum power factor is 2.73 mW/mK2 obtained with a film thickness of 9.0 µm and an applied temperature of 100 °C. Planar Sb2Te3 produced a maximum output power of 0.032 µW for a temperature difference of 58 K.
Keywords: flexible film; power factor; Sb2Te3 material; thermoelectric property